The Impact of Marine Algae on Health and Physical Performance: A Literature Review - Sikora, Gabriela; Woźniak, Martyna; Kutnik, Karolina; Koguc, Karolina; Kusibab, Karolina; Czechowski, Michał; Skórska, Gabriela; Słomianny, Marcela; Kolada, Karolina (Journal of Education, Health and Sport, 2025)
Introduction: Marine algae are rich in bioactive compounds with diverse health-promoting effects. Their ability to thrive in extreme marine environments results in the synthesis of unique metabolites. Methodology: A review was conducted using PubMed, Google Scholar, and ResearchGate. Search terms included: algae, Spirulina, Chlorella, supplement, health, sport, toxicity. Studies published between 2011 and 2024 were reviewed. Results: Algae contain compounds that exhibit antioxidant, anti-inflammatory, anticancer, neuroprotective, antimicrobial, and metabolic regulatory properties. They have demonstrated potential in improving outcomes in conditions such as diabetes, cardiovascular disorders, neurodegenerative diseases, and cancer. Additionally, Spirulina has been shown to enhance physical performance and support recovery in athletes. However, concerns regarding heavy metal accumulation and lack of product standardization have also been noted. Conclusions: Algae offer broad therapeutic potential in nutrition and both preventive and curative medicine. Nevertheless, further human studies and the development of regulatory standards are necessary to guarantee the safety and efficacy.